Digital Media Literacy in Improving Educators Tasks Based on The Islamic Education Model - Tonna Balya; Syukur Kholil; Winda Kustiawan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze digital media literacy skills, the use of digital media literacy in increasing assignments, the supporting and inhibiting factors in utilizing digital media literacy, and the successful implementation of media literacy in educators at the Potential University of Utama. The qualitative method with a descriptive approach is the method used in this research. Informants in this study were lecturers from the University of Medan Main Potential. Data was collected using interviews and documentation studies. Data is analyzed by organizing and preparing data for analysis, reading or looking at all the data, starting coding all of the data, using the coding process to generate a description, interrelating themes, and interpreting the meaning of themes. Testing the validity of the data is done through triangulation and member checks. From the results of the study, it can be seen that the Digital Media Literacy Ability of Educators in Enhancing Their Tasks at the Potential Main University of Medan is quite good because it is supported by the role of the University in creating information systems as a form of implementing digital technology development, so lecturers try to apply the use of digital technology in carrying out their jobs. Utilization of digital media literacy in improving the duties of educators at the Potential Main University of Medan is done by utilizing the information system that has been built by the university and the platform provided by Google as a platform that provides a search engine. So that by using the Islamic education model, there are many values of responsibility on the religious side that can motivate lecturers and educational staff to be able to use the system wisely in completing their assignments.